Assessment of Romania’s Tourism Competitiveness: A Strategic Analysis Using the Importance-Performance (IPA) and Competitive Importance-Performance Analysis (CIPA) Frameworks - Eugenia Andronic; Elena-Nicoleta Untaru (My University, 2025)
In today’s dynamic tourism industry, shaped by globalization and digitalization, un derstanding destination competitiveness is crucial for crafting sustainable development policies. This paper explores Romania’s competitive advantage as a tourist destination through both theoretical and practical perspectives. The present research aims to diag nose Romania’s level of competitiveness by identifying tourist attributes perceived as relevant by visitors and evaluating their performance relative to other similar European destinations. A quantitative questionnaire-based survey was conducted to achieve this goal. The survey included 235 respondents, gathered through non-probability convenience and snowball sampling. Romania’s competitiveness was assessed using the Competitive Importance-Performance Analysis (CIPA) method, which allowed for the strategic mapping of the country’s position based on the relative performance of essential attributes. These attributes included cultural heritage, the diversity of natural landscapes, the digitalization of tourism services, and staff hospitality. The results highlighted that Romania possesses significant strengths in natural landscapes, gastronomy, accommodation quality, and out door activities. However, the study identified major negative gaps in critical areas such as service digitalization, tourist staff attitude, and the quality of cultural events. These f indings underscore a latent competitive advantage based on authentic resources, which is currently underexploited from the perspective of modern management and infrastructure. The practical implications of this research provide a solid basis for optimizing tourism marketing policies, efficient resource allocation, and strengthening Romania’s positioning as an authentic, sustainable, and competitive destination within the European landscape.
Keywords: competitive advantage; Romania; competitive importance-performance analysis; tourism destination